Konsep Moral Ajaran Tat Twam Asi Dan Implementasinya Dalam Pendidikan Karakter Anak - Berliana Diah, Ni Kadek (Jayapangus Press, 2022)
Tat Twam Asi is a teaching that teaches moral concepts and love towards fellow humans. The teachings of Tat Twam Asi are one of the basic references to moral teachings in Hinduism. This research discusses (1) The concept of moral philosophy among the teachings of Tat Twam Asi, (2) Implementation of Tat Twam Asi 's teachings in children's character education. The methods used to collect data are literature study, document study, and online data search. The collected data was analyzed using qualitative methods with steps to reduce data, present data, and verify data. The analysis technique used in this research is descriptive data analysis technique. The determination of informants in this research was carried out deliberately on the basis of the researcher's knowledge and beliefs based on certain objectives. The research results show that the teachings of Tat Twam Asi in their teachings are based on the teaching of equal human dignity. The meaning of the statement of equal human dignity is that all humans are born with the same degree or dignity. Therefore, humans must love and respect each other. Love for fellow creatures of God is very important. The goal that Tat Twam Asi teachings want to achieve with its teachings about morals is to become a person who has a good personality so that it can be seen in his behavior. The meeting point of Tat Twam Asi 's teachings is maintaining social harmony, encouraging personal development, providing a foundation for one's actions, and universal brotherhood. The relevance of these two teachings is mutual respect, caring for each other, giving love and caring for others.